2004
DOI: 10.3904/kjim.2004.19.1.1
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Multiple Strain Colonization of Helicobacter pylori in Korean Patients: DNA Diversity Among Clinical Isolates from the Gastric Corpus, Antrum and Duodenum

Abstract: Background :The aims of our study were to determine the correlation of the strain variation and degree of homogeneity of infecting Helicobacter pylori (H. pylori) with their disease outcomes, and the relevance of duodenal H. pylori expression of cagA and/or vacA gene to the development of duodenal ulcer in Korean patients.Methods :One hundred and twenty bacterial colonies isolated from different anatomical sites of the stomach and duodenum were used. The study population was consisted of 40 Korean patients, 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Thus, further studies are necessary to determine whether size variation of the promoter region affects transcriptional activity of galT . Additionally, two strains showed multiple bands, indicating a mixed population of cells within the isolate, suggesting that the patient was colonized with multiple H. pylori strains or a single strain with clonal variants, phenomena that have been observed previously [43,52–55]. Alternatively, these multiple bands could be the result of intragenomic or intergenomic recombination, commonly observed in H. pylori at various loci [35,56–58], including between Le synthesis genes [44].…”
Section: Discussionmentioning
confidence: 71%
“…Thus, further studies are necessary to determine whether size variation of the promoter region affects transcriptional activity of galT . Additionally, two strains showed multiple bands, indicating a mixed population of cells within the isolate, suggesting that the patient was colonized with multiple H. pylori strains or a single strain with clonal variants, phenomena that have been observed previously [43,52–55]. Alternatively, these multiple bands could be the result of intragenomic or intergenomic recombination, commonly observed in H. pylori at various loci [35,56–58], including between Le synthesis genes [44].…”
Section: Discussionmentioning
confidence: 71%
“…In a study by Finger et al in Peru, at least 50z of patients showed infection with 2 H. pylori strains, however 61z of these patients were infected with closely related strains (19). In other studies in Korea and India, it was shown that 67.5z and 100z of the studied patients harbored multiple H. pylori strains, respectively (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Stomachs can be colonised by multiple strains (Kibria et al 2015; J. W. Kim et al 2004;Ben Mansour et al 2016). Some of the strains could have been linked to gastric cancer, when they were actually not the strains driving the carcinogenesis.…”
Section: Clonalframe Based Methods Although Well-adapted For Other Bmentioning
confidence: 99%
“…A good example of diversity can be seen by the fact that two strains of H. pylori found in different patients (or even in patients from a same family) are often extremely different (Kivi et al 2007). Different strains of H. pylori can also colonise a same host (Kibria et al 2015; J. W. Kim et al 2004;Ben Mansour et al 2016). The H. pylori genome is incredibly diverse, with variation in genome size (Dong et al 2014), gene presence, gene order, and allelic profile (Thorell et al 2016).…”
Section: H Pylori Genome Variabilitymentioning
confidence: 99%
See 1 more Smart Citation